Dramatic bone remodeling following larotrectinib administration for bone metastasis in a patient with TRK fusion congenital mesoblastic nephroma. Issue 10 (12th June 2018) - Halalsheh, Hadeel; McCarville, Mary Beth; Neel, Michael; Reynolds, Mark; Cox, Michael C.; Pappo, Alberto S.
Abstract: Mesoblastic nephroma is the most frequent renal tumor in newborns and young infants, and the cellular type is characterized by an ETV6–NTRK fusion, which constitutively activates the tropomyosin‐related kinase (TRK) signaling pathway. Larotrectinib is a highly selective TRK inhibitor with activity in adult and pediatric patients who have TRK fusions. We present a rare case of a patient with mesoblastic nephroma metastatic to bone who had a dramatic response to larotrectinib.